Environment Degradation and Sustainable Economic Development in Southeast Sulawesi - Sulaiman, Nasrullah (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes about ensure sustainable economic development in Southeast Sulawesi, environmental degradation should not increase over time and, ideally, should decrease. The mining industry is the second largest contributor to the Gross Regional Domestic Product (GRDP) of Southeast Sulawesi. However, environmental degradation also occurs due to mining activities in some areas. The literature review in this study suggests that the government needs to take policy measures to address environmental degradation caused by mining activities in several areas of Southeast Sulawesi. Reclamation of former mining areas is an appropriate policy that can be implemented by the government to address environmental degradation resulting from mining activities without regard to proper mining processes, thereby minimising the impact of environmental degradation that can harm communities and damage the environment.